Asymptotic solutions of boundary value problem for singularly perturbed system of differential-algebraic equations - Samusenko, P.F.; Vira, M.B. (Carpathian Mathematical Publications, 2022)
This paper deals with the boundary value problem for a singularly perturbed system of differential algebraic equations of the second order. The case of simple roots of the characteristic equation is studied. The sufficient conditions for existence and uniqueness of a solution of the boundary value problem for system of differential algebraic equations are found. Technique of constructing the asymptotic solutions is developed.